Extractive metallurgy of copper - Schlesinger, Mark E.; King, Matthew J.; Sole, Kathryn C.; Davenport, W. G. (William George) (Amsterdam ; Boston : Elsevier, 2011)
"This multi-author new edition revises and updates the classic reference by William G. Davenport et al (winner of, among other awards, the 2003 AIME Mineral Industry Educator of the Year Award "for inspiring students in the pursuit of clarity"), providing fully updated coverage of the copper production process, encompassing topics as diverse as environmental technology for wind and solar energy transmission, treatment of waste by-products, and recycling of electronic scrap for potential alternative technology implementation. The authors examine industrially grounded treatments of process fundamentals and the beneficiation of raw materials, smelting and converting, hydrometallurgical processes, and refining technology for a mine-to-market perspective - from primary and secondary raw materials extraction to shipping of rod or billet to customers. The modern coverage of the work includes bath smelting processes such as Ausmelt and Isasmelt, which have become state-of-the-art in sulfide concentrate smelting and converting."--Publisher's description.
Fire refining (S and O removal) and anode casting. Industrial methods of fire refining. Chemistry of fire refining. Choice of hydrocarbon for deoxidation. Casting anodes. Continuous anode casting. New anodes from rejects and anode scrap. Removal of impurities during fire refining -- Electrolytic Refining. The electrorefining process. Chemistry of electrorefining and behavior of anode impurities. Equipment. Typical refining cycle. Electrolyte. Maximizing copper cathode purity. Minimizing energy consumption. Industrial electrorefining. Recent developments and emerging trends in copper electrorefining -- Hydrometallurgical copper extraction: introduction and leaching. Copper recovery by hydrometallurgical flowsheets. Chemistry of the leaching of copper minerals. Leaching methods. Heap and dump leaching. Vat leaching. Agitation leaching. Pressure oxidation leaching. Future developments -- Solvent extraction. The solvent-extraction process. Chemistry of copper solvent extraction. Composition of the organic phase. Minimizing impurity transfer and maximizing electrolyte purity. Equipment. Circuit configurations. Quantitative design of a series circuit. Quantitative comparison of series and series-parallel circuits. Operational considerations. Industrial solvent-extraction plants -- Electrowinning. The electrowinning process. Chemistry of copper electrowinning. Electrical requirements. Equipment and operational practice. Maximizing copper purity. Maximizing energy efficiency. Modern industrial electrowinning plants. Electrowinning from agitated leach solutions. Current and future developments -- Collection and processing of recycled copper. The materials cycle. Secondary copper grades and definitions. Scrap processing and beneficiation -- Chemical metallurgy of copper recycling. Characteristics of secondary copper. Scrap processing in primary copper smelters. The secondary copper smelter -- Melting and casting. Product grades and quality. Melting technology. Casting machines -- Byproduct and waste streams. Molybdenite recovery and processing. Flotation reagents. Operation. Optimization. Anode slimes. Dust treatment. Use or disposal of slag -- Costs of copper production. Investment costs: mine through refinery. Overall direct operating costs: mine through refinery. Total production costs, selling prices, profitability. Concentrating costs. Smelting costs. Electrorefining costs. Production of copper from scrap. Leach/solvent extraction/electrowinning costs. Profitability.
Includes bibliographical references and index.
Print version record and online resource; title from PDF title page (EBSCOhost eBook Collection, viewed Oct. 14, 2013).
Added to collection customer.56279.3
Keywords: Copper -- Metallurgy; Cuivre -- Métallurgie; TECHNOLOGY & ENGINEERING -- Metallurgy; Copper -- Metallurgy